Synergistic prevention of biofouling in seawater desalination by zwitterionic surfaces and low-level chlorination - Yang, Rong (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.